DETERMINATION OF ACTIVE INGREDIENT IN TAMSULOSIN DRUG BY USING HPLC - Al-Shammari, W T. H.; Al- Ogaidi, A. J. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to development and modification the method of analysis for active ingredient in Tamsulosin drug by using high performance liquid chromatography (HPLC) also determined shelf life and storage conditions for Tamsulosin. Chromatographic conditions utilized stationary phase C18 (250*4.6) mobile phase 0.05Nmixture of  di hydrogen ortho phosphate and Acetonitrile 55:45 , preserve the flow rate near (1ml/min) and length of wave has been 275nm, The retention time found to be 10 minute for the HPLC process . The Tamsulosin assay result was found to be 99.93% . The calibration curve linearity analysis results showed a strong linear relationship in the concentration range (10-200ppm) and the correlation coefficient, slope and intercept value were 0.9933,11796,190017, respectively The percentage recovery was found 99%. LOD value was found to 0.00053 µg/ml  and LOQ value was found to 0.0016 µg/ml , Precision was found to be 99.49% Robustness was found to 99.69%. Our proposed procedure confirmed a group of merits such as  Linear ,accurate ,precise ,and robust , could be recommended for determination of Tamsulosin.